Experimental Behavior of Circular Steel Tubular Columns Filled with Self-Compacting Concrete under Concentric Load - Saad N. Sadik; Wael S. Abdul-Sahib; Ammar A. Ali (Engineering and Technology Journal, 2013)
This paper presents an experimental study on the behavior of circular, concretefilled,steel tube (CFT) columns concentrically loaded in compression to failure. Selfcompactingconcrete (SCC) is used here as a filler in order to increase homogeneity ofthe core and reduce segregation problems. Total six column specimens with differentlengths (0.4 m – 1.5 m) of constant diameter of 160 mm and wall thickness of 2.8 mmwere tested. The purpose here is to investigate the ultimate capacity and thedeformation behavior of different slenderness ratio columns. The behavior of thesecolumns in confinement was discussed.Experimental results indicate that the compression force capacity is affected byslenderness ratio of the column. For slender column the overall buckling was observedwhile for the short columns the crushing and the local buckling is the dominant failureshape.